2016
DOI: 10.2196/jmir.6307
|View full text |Cite
|
Sign up to set email alerts
|

Using Intensive Longitudinal Data Collected via Mobile Phone to Detect Imminent Lapse in Smokers Undergoing a Scheduled Quit Attempt

Abstract: BackgroundMobile phone‒based real-time ecological momentary assessments (EMAs) have been used to record health risk behaviors, and antecedents to those behaviors, as they occur in near real time.ObjectiveThe objective of this study was to determine if intensive longitudinal data, collected via mobile phone, could be used to identify imminent risk for smoking lapse among socioeconomically disadvantaged smokers seeking smoking cessation treatment.MethodsParticipants were recruited into a randomized controlled sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 42 publications
6
68
2
Order By: Relevance
“…For example, in smokers attempting to quit, Shiffman and Waters (2004) found that lapses followed rapid rises in negative mood, on the order of hours, but not on the order of whole days. Businelle and colleagues (2016) also found increases in specific risk factors within four hours of patients’ first smoking lapse. Our group has shown that, in cocaine and heroin users on opioid agonist maintenance, exposure to putative risk factors increases in the hours leading up to cocaine use, but less so for heroin use (Epstein et al 2009).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, in smokers attempting to quit, Shiffman and Waters (2004) found that lapses followed rapid rises in negative mood, on the order of hours, but not on the order of whole days. Businelle and colleagues (2016) also found increases in specific risk factors within four hours of patients’ first smoking lapse. Our group has shown that, in cocaine and heroin users on opioid agonist maintenance, exposure to putative risk factors increases in the hours leading up to cocaine use, but less so for heroin use (Epstein et al 2009).…”
Section: Introductionmentioning
confidence: 78%
“…Researchers have been investigating the use of EMA data to predict future drug use. For example, Businelle and colleagues (2016) found that risk factors were higher within four hours of patients’ first smoking lapse and that EMA was promising as a tool to estimate the likelihood of lapse and automate delivery of tailored smoking cessation treatment. Mobile treatment might provide a path to improved treatment efficacy as well as making treatment available to areas where treatment programs are geographically remote and extend treatment beyond the usual duration of clinician contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 2-week postquit period, participants received individually tailored automated messages based on their EMA responses (see [35] for a complete description of the lapse risk estimator). Level 1 messages were delivered when EMA responses indicated a low level of imminent smoking lapse risk, and message content focused on maintaining abstinence motivation and general cessation advice (eg, seeking social support for cessation, coping with various lapse triggers, and benefits of quitting).…”
Section: Methodsmentioning
confidence: 99%
“…The EMA methodology that will be used in this study is similar to that developed by Shiffman and colleagues [51,67,68] and was used in previous studies conducted by the investigative team. [69][70][71][72][73] EMA items will assess numerous constructs that are hypothesized to be related to the study outcomes (see Table 3). The phone will audibly and visually cue EMAs for five minutes, 30 minutes after each participant's pre-set waking time.…”
Section: Programming the Mhealth Shared Resource At The Ouhsc And Stmentioning
confidence: 99%